Evaluating the affordances of fishing village pertaining to children’s functioning - Said, Ismail (Penerbit UTM, 2007)
This study presents an evaluation on the affordances of fishing village pertaining to the behaviours of children. It analysed the physical properties of the natural landscape and architecture of the village and social attributes which influenced the routine behaviours of the village children. Seventy-six children, aged 2-12, from a fishing village in Sabah, Malaysia were observed. Data of their behavioural responses, movements and words, toward the landscape and architecture of the village. The former were elicited from participatory observation and the latter were gathered from open-ended interview. The data was analysed in three stages: (i) positive and negative affordances, (ii) taxonomy of affordances, and (iii) types of children’s activities. The children experienced 78 positive affordances and only 2 negative ones. From the taxonomy, graspable objects and water offered the most positive affordances, 20 and 15, respectively. And, the largest percentage of activities (70%) was the performatory ones. The results suggest the children effectively perceived the fishing as a playspace which was sensorially rich and varied; affording them complex and diverse natural and man-made properties for social play and affection to the fishing village. This finding implicates that development of coastal community should consider the behavioural responses of the children in relation to their perception, physical movement and social interaction.